Islamic Economics and Finance in India: Opportunities and Obstacles - Muzafar Ahmad Mir (Penerbit Hellow Pustaka, 2025)
Islamic economics and finance have gained momentum globally due to the increasing demand for financial products that are aligned with Islamic principles. Islamic economics and finance have gained significant attention in India in recent years, with the Muslim population comprising approximately 14% of the total population. However, the implementation of Islamic finance in India faces several obstacles, including a lack of regulatory framework, the absence of a legal framework and tax incentives, and a lack of awareness and education about Islamic finance. These obstacles lead to a lack of demand for Islamic financial transactions and services. The paper concludes that the development of Islamic finance in India has significant potential for the country’s financial sector but requires a comprehensive approach that addresses the legal, regulatory, and social challenges. The country’s large Muslim population is underserved by the traditional banking system. Islamic finance could provide an alternative to conventional banking for this population. Moreover, the Indian government’s recent push toward financial inclusion provides a platform for Islamic finance to contribute to the country’s economic development. The present study will analyze the opportunities and obstacles in Islamic economics and finance in India by using mixed methods and political economy approaches in research methodology.